A Review of Geotourism and Geoparks: Is Africa missing out on this new mechanism for the development of sustainable tourism? - Percy Mabvuto Ngwira (Geoconservation Research)
This paper uses sustainable tourism development paradigm to demonstrate the economic, social-cultural and environmental potentialities presented by ‘Geotourism’ and its primary product ‘Geoparks’ in the quest for sustainable tourism development in Africa. Utilising secondary data sources, this study finds that; geotourism and geoparks are a relatively new phenomenon and subdivisions of geology and tourism. Though arguably still in the infancy stage and emerging as tourism niche markets awaiting further development and commercialisation, geotourism and geoparks have been credited as tools for sustainable tourism development with fundamental credentials to contribute to environmental, social-cultural and economic development for rural communities. Further findings indicate that despite Africa possessing so much geomorphological features and tourism potential the continent is lagging in exploiting opportunities presented by the geotourism and geoparks development. Therefore, this scholarship attempts to identify and examine sustainable tourism opportunities presented by geotourism and geoparks. Also, Africa’s challenges in the development of geotourism and geoparks are examined and the way forward proposed. The scholarship is valuable to tourism policy makers, planners, development practitioners and other tourism stakeholders in Africa.